Cellular Localization of Nectin-1 and Glycoprotein D during Herpes Simplex Virus Infection - Krummenacher, Claude (American Society for Microbiology, 2003)
During viral entry, herpes simplex virus (HSV) glycoprotein D (gD) interacts with a specific cellular receptor such as nectin-1 (PRR1/HveC/CD111) or the herpesvirus entry mediator A (HVEM/HveA). Nectin-1 is involved in cell-to-cell adhesion. It is located at adherens junctions, where it bridges cells through homophilic or heterophilic interactions with other nectins. Binding of HSV gD prevents nectin-1-mediated cell aggregation. Since HSV gD affects the natural function of nectin-1, we further investigated the effects of gD expression on nectin-1 during HSV infection or in transfected cells. We also studied the importance of the interaction between nectin-1 and the cytoplasmic protein afadin for HSV entry and spread as well as the effects of infection on this interaction. In these investigations, we used a panel of cells expressing nectin-1 or nectin-1-green fluorescent protein fusions as the only mediators of HSV entry. During HSV infection, nectin-1 localization at adherens junction was dramatically altered in a manner dependent on gD expression. Nectin-1 and gD colocalized at cell contact areas between infected and noninfected cells and at the edges of plaques. This specific accumulation of gD at junctions was driven by expression of nectin-1 in trans on the surface of adjacent cells. Reciprocally, nectin-1 was maintained at junctions by the trans expression of gD in the absence of a cellular natural ligand. Our observations indicate that newly synthesized gD substitutes for nectin-1 of infected cells at junctions with noninfected cells. We propose that gD attracts and maintains the receptor at junctions where it can be used for virus spread.